Integrasi Tradisi Nyadran dalam Materi Teks Deskripsi: Pengembangan Media Pembelajaran Board Game untuk Siswa SMP - Chaesar, Ari Suryawati Secio; Andayani, Andayani; Yulisetiani, Septi (SAWERIGADING, 2025)
The descriptive text is one of the important learning materials in Indonesian language lessons for seventh-grade junior high school students. However, there are still several problems that occur in the learning process of descriptive texts. Based on the analysis of these learning problems, it was found that no innovative learning media have been optimally utilized. In addition, the learning of descriptive texts still relies heavily on textbooks, making it less contextual. Therefore, developing a board game as a learning medium for descriptive texts that integrates local wisdom is important. The method used is research and development (RD) with the ADDIE model. The product was validated by experts, including material experts, learning media experts, and practitioners. Furthermore, at the evaluation stage, user response tests involving teachers and students were conducted to assess the board game medium. Based on the product validation and response tests, the board game learning medium was declared feasible for use. AbstrakThe descriptive text is one of the important learning materials in Indonesian language lessons for seventh-grade junior high school students. However, there are still several problems that occur in the learning process of descriptive texts. Based on the analysis of these learning problems, it was found that no innovative learning media have been optimally utilized. In addition, the learning of descriptive texts still relies heavily on textbooks, making it less contextual. Therefore, developing a board game as a learning medium for descriptive texts that integrates local wisdom is important. The method used is research and development (RD) with the ADDIE model. The product was validated by experts, including material experts, learning media experts, and practitioners. Furthermore, at the evaluation stage, user response tests involving teachers and students were conducted to assess the board game medium. Based on the product validation and response tests, the board game learning medium was declared feasible for use.